Мобільні засоби оцінки вібраційного стану енергетичних агрегатів - Шульженко, М. Г.; Єфремов, Ю. Г.; Цибулько, В. Й.; Депарма, О. В. (НТУ "ХПІ", 2014)
Описано апаратні засоби мобільного багатофункціонального вимірювально-діагностичного комплексу неруйнівного контролю й оцінки технічного стану енергетичних і транспортних агрегатів тривалої експлуатації. Наведено технічні характеристики й функціональні можливості мобільних пристроїв оперативного контролю й аналізу вібростану устаткування. Наведено приклад використання розробленого мобільного комплексу при діагностуванні причин підвищеної вібрації турбоагрегату К-200-130. Результати можуть застосовуватися при рішенні завдань вібродіагностики й встановлення причин підвищеної вібрації енергетичних агрегатів.

The hardware used by the mobile multifunctional measuring-&-diagnostic system for the nondestructive control and assessment of the technical state of power and transport units of a continuous service has been described. The technical performances and functional possibilities of mobile units used for the online control and analysis of the vibratory state of the equipment, in particular rotation frequency measurement (vibrometer); determining the imbalance sites of rigid rotors (the balancing device) have been given. The described tools can be used both as offline measuring devices and as the part of mobile and stationary systems to diagnose the vibratory state of the units. An example of the use of the developed mobile system to diagnose the reasons for the increased vibration of turbounit K-200-130 has been given. The obtained results can be used to solve the problems related to vibrodiagnostics and to establish the reasons for an increased vibration of power units.
Mobile tools used for the assessment of the vibratory state of power units
Keywords: вихорострумовий датчик; перетворювач; система діагностики; vortex sensor; converter; vibration; vibration state; diagnostics system